On Concepts and Measures of Changes in Productivity - Pasinetti, Luigi L. (The Review of Economics and Statistics, 1959)
T-flECHNICAL progress has received unprecedented attention by economists in the last few decades, but more because statistical evidence has imposed the subject on them than as a spontaneous development of economic thought. Indeed, the whole neo-classical movement and the increasing modern application of mathematics, which have contributed so much to improving the tools of economic analysis and to conferring rigor and definiteness on economic thought, have preferred to leave technical progress aside. The trouble is that technical changes are hard variables to deal with in analytical terms. The statistical data which have appeared in the last few decades have come as quite a surprise to economists, because their theories, from the Ricardian to the neo-classical, did not lead them to expect such results. I refer in particular to some statistical evidence for the United States and for other capitalistic countries which has shown that, on the average and in the long run, shares of labor and capital in the national product have not changed very much, that wages have not remained at the subsistence level but have risen in proportion to national income, that capital per man has indeed increased but output per man has also increased in proportion, that the rate of remuneration of capital has remained almost constant. In the absence of an economic theory giving a straightforward interpretation of all these outcomes the attention of economists has been called back more and more to changes in technology; and economic statisticians, in trying to evaluate these changes, have followed the easiest way: they have normally taken ratios of production to man-hours (labor productivities) and computed their changes through time. The procedure is very useful for many purposes but, among other limitations for example, the impossibility of taking into account qualitative improvements it has the major defect of referring only to labor, while the production process involves as well other factors of production whose productivity might change in a different way. This leads to different conclusions as to the productivity of the system as a whole. There have been some attempts by economists to complete these evaluations and to introduce capital into the picture, by making use of theoretical notions like the production function, but these attempts in the writer's opinion have neglected an important characteristic of capital that it is reproducible and that its process of production is also subject to technical change. It is my purpose in this paper to go into these problems. I shall try to give a short theoretical economic interpretation of technical change and suggest a procedure for evaluating it, with respect to all factors of production. When particular studies about qualitative improvements are available they may be incorporated in the same framework.